Unspoken Motivation: Investigating Speaking Difficulties and Language Interference Among Indonesian EFL Students - Mahmudah, Khotimah; Hastowohadi; Rakerda, Hilda (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Understanding the reasons behind Speech Difficulties and Language Interference is a very urgent matter to address amidst the ease of access to learning English. This study investigates the challenges faced by Indonesian university students majoring in English Education in speaking English fluently. Despite having completed more than six semesters, many still mix Indonesian and English during conversations and show reluctance to use English with peers. Through semi-structured interviews with ten students preparing for teaching internships, this research explores motivational, linguistic, and sociocultural factors contributing to their speaking difficulties. The findings reveal a lack of speaking confidence, limited exposure to English input, and negative perceptions about accent and dialect as primary obstacles. Moreover, external factors such as minimal digital access in rural areas and parental pressure to enrol in the English program significantly reduce students' motivation. This study calls for a re-evaluation of English language pedagogy in teacher training programs by integrating motivational and sociolinguistic awareness.